Adele Bei
note: Pubblicata su «Lavoro», n. 3, 1956. descrizione: Fototessera di Bei, segretaria generale del Sindacato Nazionale Tabacchine. note: Pubblicata su «Lavoro», n. 3, 1956. note: Pubblicata su «Lavoro», n. 3, 1956. note: Pubblicata su «Lavoro», n. 3, 1956.